2002
DOI: 10.1002/jnr.10111.abs
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of thyroid hormone receptor isoforms in mouse oligodendrocytes

Abstract: Double and triple immunocytochemistry with stage-specific markers and specific antireceptor antibodies was used to study expression of nuclear thyroid hormone receptor (TR) isoforms in cultured mouse oligodendrocytes. To evaluate the coexpression of each TR isoform, antibodies were raised in rabbits and mice against specific regions of alpha1-TR and alpha2-TR common to both alpha isoforms and beta1-TR. Their specificities were assessed by Western blotting and by immunocytochemistry on rat hepatocytes. Oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…THRb1 expression within the oligodendrocyte lineage has been somewhat controversial. While some groups (Baas et al, 1994a,b;Billon et al, 2001Billon et al, , 2002Bury et al, 2002) report expression in differentiated OLs but not OPCs, others have found THRb1 to be present in both cell types (Barres et al, 1994). These discrepant findings may be explained by changes in the expression of THRb1 within OPCs that are dependent on the "age" of the cell.…”
Section: Role Of Thrb1 In Oligodendrocyte Maturation and Myelinationmentioning
confidence: 99%
“…THRb1 expression within the oligodendrocyte lineage has been somewhat controversial. While some groups (Baas et al, 1994a,b;Billon et al, 2001Billon et al, , 2002Bury et al, 2002) report expression in differentiated OLs but not OPCs, others have found THRb1 to be present in both cell types (Barres et al, 1994). These discrepant findings may be explained by changes in the expression of THRb1 within OPCs that are dependent on the "age" of the cell.…”
Section: Role Of Thrb1 In Oligodendrocyte Maturation and Myelinationmentioning
confidence: 99%
“…Thyroid hormones regulate brain development as attested by severe morphological, functional and cognitive impairments monitored in congenitally hypothyroid infants (Oppenheimer and Schwartz 1997). Particularly, they ensure normal oligodendrocyte maturation and myelination (McIntosh et al, 1981;Baas et al, 1997;Rodríguez-Peña 1999;Bury et al, 2002). There are two circulating thyroid hormones: thyroxin (T 4 ) and T 3 , and their action is transduced by thyroid hormone receptors (TRs), expressed in different cell types, including precursors and mature oligodendrocytes.…”
Section: Remyelination Induced By T 3 -Based Therapymentioning
confidence: 99%
“…There appears to be general consensus that both OPCs and OLGs express TRa and that OLGs express TRb (Carr e et al, 1998;Fierro-Renoy, 1995), in agreement with Bury et al (2002), who showed that TRa and TRb colocalize in OLGs before CNPase is expressed. Very recently, Baxi et al (2014) showed that a TRb agonist promotes oligodendrogenesis in rodents and in human OPCs in vitro.…”
Section: Discussionmentioning
confidence: 57%